Stop, think, reflect, realize-first‐time mothers' views on taking part in longitudinal maternal health research - Deirdre Daly; Margaret Carroll; Monalisa Barros; Cecily Begley (Wiley, 2019)
Abstract Background Longitudinal cohort studies gather large amounts of data over time, often without direct benefit to participants. A positive experience may encourage retention in the study, and participants may benefit in unanticipated ways. Objective To explore first‐time mothers' experiences of taking part in a longitudinal cohort study and completing self‐administered surveys during pregnancy and at 3, 6, 9 and 12 months' postpartum. Design Content analysis of comments written by participants in the Maternal health And Maternal Morbidity in Ireland study's five self‐completion surveys, a multisite cohort study exploring women's health and health problems during and after pregnancy. This paper focuses on what women wrote about taking part in the research. Ethical approval was granted by the site hospitals and university. Setting and participants A total of 2174 women were recruited from two maternity hospitals in Ireland between 2012 and 2015. Findings A total of 1000 comments were made in the five surveys. Antenatally, barriers related to surveys being long and questions being intimate. Postpartum, barriers related to being busy with life as first‐time mothers. Benefits gained included gaining access to information, taking time to reflect, stopping to think and being prompted to seek help. Survey questions alone were described as valuable sources of information. Discussion and conclusions Findings suggest that survey research can "give back" to women by being a source of information and a trigger to seek professional help, even while asking sensitive questions. Understanding this can help researchers construct surveys to maximize benefits, real and potential, for participants.